1993
DOI: 10.1017/s0031182000067755
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Trypanosoma cruzi populations from Argentina estimated from enzyme polymorphism

Abstract: Isolates of Trypanosoma cruzi from human patients, domestic and sylvatic animals and vector insects were obtained in different areas of Argentina. Electrophoretic patterns of enzymes from extracts of 95 isolates were analysed. On the basis of zymograms providing information on 10 loci, 12 zymodemes are described according to their genotypes. Data presented show fixed heterozygosity, absence of segregation of genotypes, significant departures from Hardy-Weinberg equilibrium, and over-represented genotypes. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…In the late 1980s, when intense domestic transmission of T. cruzi was prevalent and widespread, sylvatic mammals (opossums, ferrets and skunks) were sometimes found infected with TC IId, which also infected domestic dogs and Tr. infestans in Santiago del Estero (Wisnivesky-Colli et al, 1992;De Luca d'Oro et al, 1993). In such an epidemiological context of intense transmission, the observed distribution of lineages was probably a spillover of parasite strains from domestic into sylvatic habitats.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In the late 1980s, when intense domestic transmission of T. cruzi was prevalent and widespread, sylvatic mammals (opossums, ferrets and skunks) were sometimes found infected with TC IId, which also infected domestic dogs and Tr. infestans in Santiago del Estero (Wisnivesky-Colli et al, 1992;De Luca d'Oro et al, 1993). In such an epidemiological context of intense transmission, the observed distribution of lineages was probably a spillover of parasite strains from domestic into sylvatic habitats.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies based on MLEE concluded that domestic and sylvatic transmission cycles of T. cruzi overlapped partially throughout Argentina including rural areas within the Chaco region (Wisnivesky-Colli et al, 1992;De Luca d'Oro et al, 1993;Diosque et al, 2003). In the late 1980s, when intense domestic transmission of T. cruzi was prevalent and widespread, sylvatic mammals (opossums, ferrets and skunks) were sometimes found infected with TC IId, which also infected domestic dogs and Tr.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations